Satisfaction with general functionality and safety of travel in relation to residential environment and satisfaction with transport modes - Hanne Tiikkaja (European Transport Research Review, 2020)
Abstract The objective of this paper is to study 1) do people living in certain residential environments express more dissatisfaction with general functionality and safety of travel, 2) is dissatisfaction with general functionality and safety of travel related to dissatisfaction with certain transport modes, 3) is the residential environment related to mode-specific travel satisfaction mediated by satisfaction with general functionality and safety of travel, and 4) is dissatisfaction with general functionality and safety of travel related to use of different transport modes. The analyses are based on a Finnish survey (representative sample of 17,996 people, response rate 29.7%) on citizen satisfaction with the transport system and travel chains. Three groups, the satisfied, the neither satisfied nor dissatisfied and the dissatisfied, are analysed according to their residential environment, satisfaction with different transport modes and the use of the modes. The results indicate that the residential environment and the satisfaction with general functionality and safety of travel are related. Results suggest that satisfaction with different modes is partly related to lower options offered by the residential environment and higher expectations towards the residential environment. However, satisfaction with general functionality and safety of travel does not relate to higher expectations in a similar way. Findings from this study indicate that satisfaction with daily travel is a phenomenon related to the travel options offered by the residential environment.